Drunk, Drugged and Disorderly: Examining the Non-Linear Effects of Neighborhood Racial Composition on Race-Specific Arrests. (19th September 2022) - Chamberlain, Alyssa W.; Boggess, Lyndsay N.; Walker, Jason
Abstract: Neighborhood racial composition contributes to racial disparities in arrests, but prior research has almost exclusively focused on the magnitude of a minority population with somewhat mixed findings. We investigate whether racial disparities in arrests perpetuate when the racial composition reaches a particular threshold to assess whether the accumulation of race matters, and to what degree. To expand upon prior research, we include a range of part 2 crimes—public drunkenness, drug offenses, and disorderly conduct—"lower level" crimes which may allow for greater police discretion. We conduct negative binomial regression analyses using arrest data from a mid-sized city in the South between 2010 and 2015. Results show evidence of a threshold effect, but this pattern differs across race and crime type. This suggests that race-specific arrest rates may be driven by offense type and neighborhood racial composition.